An Uncommon Cause of Cardiac Arrest: Tamponade Secondary to Malignant Pericardial Effusion From Myxoid Sarcoma - Marianna Weaver; James Bradley; Shahab Ghafghazi; Christopher Fine (Annals of Internal Medicine: Clinical Cases)
Primary tumors involving the pericardium are rare and often are incidentally discovered with transthoracic echocardiography. These tumors cause complications from obstruction of cardiac function with hemodynamic instability. We present a case of a 30-year-old man with primary myxoid sarcoma that resulted in cardiac arrest from malignant pericardial effusion. Despite partial resection and chemotherapy, the patient died. Despite being rare, with a 2-year survival of 60%, it is important for clinicians to be able to recognize complications from this tumor. Although no formal guidelines exist, performing surveillance echocardiography in this patient population could prevent some complications.